Absorption cross sections for neopentane broadened by nitrogen in the 3.3 µm region. (August 2020) - Bernath, Peter; Dodangodage, Randika; Dulick, Michael; Zhao, Jianbao; Billinghurst, Brant
Highlights: High resolution absorption spectra of neopentane, C(CH3 )4, in the 3.3 µm region (2550-3350 cm -1 ). Cross sections for neopentane broadened by N2 . Measurements performed for 202-297 K. Useful for analysis of spectra of Titan. Abstract: Infrared absorption spectra of neopentane, 2, 2-dimethylpropane, C(CH3 )4, were recorded in the 2550-3350 cm -1 region by high resolution Fourier transform spectroscopy at the Canadian Light Source (CLS). Absorption cross sections were obtained for pure samples and with nitrogen as a broadening gas for 4 temperatures (202, 232, 265, 297 K).